Infection prevention in the immunocompromised traveler due to conditions other than transplantation: a review - Joseph Sassine; Emily A. Siegrist; Rita Wilson Dib; José Henao-Cordero; Nelson Iván Agudelo Higuita (Therapeutic Advances in Infectious Disease)
This narrative review explores the risks related to infection in immunocompromised travelers due to conditions other than transplantation, and evaluates the evidence behind current prophylactic strategies, including immunizations, antimicrobials, and non-pharmacological interventions, to prevent various infection and how the current evidence applies to this special patient population, from the perspective of a US-based traveler.